PEMBERIAN STIMULAN ETEFON DENGAN TEKNIK BARK APPLICATION PADA PRODUKSI LATEKS TANAMAN KARET (Hevea brasiliensis Muell Arg.) - Tri Wulandari; Sampoerno '; M. Amrul Khoiri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research intent to know the effect of giving ethephon stimulant to the latex production of rubber plant with bark application technique. Research conducted in plantation of people rubber, Countryside of Bencah Kelubi, District of Tapung, Regency of Kampar from February till March 2015. This research  arranged experimentally by using Completely Randomized Block Design which consist of  5 treatments ( without giving of ethephon, giving dose of ethephon 0,3 cc plant-1, giving dose of ethephon 0,6 cc plant-1, giving dose of ethephon 0,9 cc plant-1, giving dose of ethephon 1,2 cc plant-1) and 4 group then obtained 20 experimental units with 3 tree each every unit. Parameter observed duration of latex flow, volume of latex and Dry Rubber Content. Data analyzed statistically using ANOVA and followed with LSD at level 5% if the results of analysis of variance significant. Result of research indicate that giving of ethephon stimulant with dose 0,9 cc plant-1 tend to increase parameters duration of latex flow and latex volume of local clone rubber. Keywords : Hevea brasiliensis Muell Arg., ethephon, bark application